A Rapid Microfluidic Platform with Real-time Fluorescence Detection System for Molecular Diagnosis. Issue 1 (1st January 2019) - Li, Zhigang; Zhao, Jun; Wu, Xiaosong; Zhu, Cancan; Liu, Yong; Wang, An; Deng, Guoqing; Zhu, Ling
Abstract: The development of microfluidics-based quantitative real-time polymerase chain reaction for molecular diagnosis is becoming a burgeoning field of research. Here, we present a compact microfluidic real-time PCR platform integrated with a thermal cycler and an online fluorescence detection module, including a disposable microfluidic chip fabricated in polydimethylsiloxane. The fluorescence detection module is able to continuously monitor the PCR reaction in the microfluidic chip over thermal cycles, and a large amount of signal data can be rapidly analysed by a built-in computer. In order to further evaluate the performance of the developed PCR platform, we carried out a series of systemic verifications, such as precision of temperature control, sensitivity and specificity. Under the optimal conditions, the limit of detection of the target molecule reached approximately 1.0 × 10 2  copies/µL, with a correlation coefficient of 0.9966. In addition, hepatitis B virus could be detected quickly by this real-time PCR system in about half an hour. Furthermore, the faint target fluorescence signal emitted from the digital microfluidic chip, which contains thousands of micro-reaction chambers with a volume of 100 pL, could be easily detected on this microfluidic platform. Overall, the results indicated that the developed microfluidic PCR platform can be used for sensitive and specific detection in molecular diagnosis. More importantly, owing to adopting the pattern of modularization design, this platform is considerably compact and portable. If necessary, special custom-made chips could be cooperated with this portable platform to satisfy the needs of various molecular detection tests.